Silangan rising crafting the Filipino self and the other in the diaspora - Malek, Jon G. (Philippine studies : historical and ethnographic viewpoints, 2019)
"This article examines the newspaper Silangan, published in Winnipeg, Canada, from February 1977 to July 1982, to analyze the negotiation of Filipino identity in the diaspora. Over its six-year run, the columns in this newspaper dealt with issues of cultural maintenance, the importance of Filipino heritage, and political engagement in their adoptive homeland. A critical dialogue argued in support of certain aspects of life from the Philippines, such as extravagant pageantry and corrupt political practices. In discursively forming a Filipino self, this ethnic newspaper created a number of Others, the most startling of which was the (transgressing) national Filipino."